2020
DOI: 10.3390/su12031228
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Intensification? Increased Production Diminishes Omega-3 Content of Sheep Milk

Abstract: Intensifying agricultural production alters food composition, but this is often ignored when assessing system sustainability. However, this could compromise consumer health and influence the concept of "sustainable diets". Here, we consider the milk composition of Mediterranean dairy sheep, finding inferior fatty acid (FA) profiles with respect to consumer health as a result of a more intensive system of production. Semi-intensive management produced 57% more milk per ewe, with a 20% lower fat content (but inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The finding of 30% to 50% higher milk yield, but lower milk fat, lactose and non-fat solid concentrations in SI compared to EX-managed ewes in this study is consistent with the results of previous studies that compared milk yield/ewe and protein, fat and lactose content in bulk milk samples in the same region of Crete [16] and other regions [3,60]. This was reported to be mainly due to the higher concentrate and lower grazing time on natural pastures [16], and this view is supported by the results of the redundancy analysis of data from this study (see Section 3.3.3 below).…”
Section: Milk Yield and Basic Composition Fat Protein And Lactose Contentsupporting
confidence: 93%
See 3 more Smart Citations
“…The finding of 30% to 50% higher milk yield, but lower milk fat, lactose and non-fat solid concentrations in SI compared to EX-managed ewes in this study is consistent with the results of previous studies that compared milk yield/ewe and protein, fat and lactose content in bulk milk samples in the same region of Crete [16] and other regions [3,60]. This was reported to be mainly due to the higher concentrate and lower grazing time on natural pastures [16], and this view is supported by the results of the redundancy analysis of data from this study (see Section 3.3.3 below).…”
Section: Milk Yield and Basic Composition Fat Protein And Lactose Contentsupporting
confidence: 93%
“…There is limited information on the effects of intensification practices on the nutritional quality of milk from small ruminants [16] and the study reported here, for the first time comparing the relative effects of dietary, management and animal health parameters on sheep milk composition. However, the results obtained for omega-3 fatty acid in this study are broadly consistent with recent studies comparing different bovine dairy production systems that showed that low-input/organic production methods result in higher ALA and VLC omega-3 concentrations in milk compared to conventional intensive production systems [69].…”
Section: Associations Between Environmental/agronomic Factors and Milk Yield/qualitymentioning
confidence: 97%
See 2 more Smart Citations
“…It is important to consider that there is also increasing evidence that the intensification of conventional livestock production had negative effects on the nutritional composition of both milk and meat [222,[241][242][243][244][245][246][247][248][249][250][251]. For example, studies which compared low-input and/or organic with intensive conventional livestock production systems have shown that the increased use of (i) cereal and grain/legume-based concentrate feeds, (ii) indoor production, (iii) high-yield potential dairy breeds, (iv) selection for high milk yield within breeds, and/or (iv) robotic milking systems in conventional systems may:…”
Section: Agricultural Intensification Practices Have Reduced Food Quality and Safetymentioning
confidence: 99%